2020
DOI: 10.1111/jne.12889
|View full text |Cite
|
Sign up to set email alerts
|

Impaired prolactin transport into the brain and functional responses to prolactin in aged male mice

Abstract: Ageing is related to changes in a number of endocrine systems that impact on the central actions of hormones. The anterior pituitary hormone prolactin is present in the circulation in both males and females, with widespread expression of the prolactin receptor throughout the forebrain. We aimed to investigate prolactin transport into the brain, as well as circulating levels of prolactin and functional responses to prolactin, in aged male mice (23 months). Transport of 125I‐labelled prolactin (125I‐prolactin) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
7
2
Order By: Relevance
“…This lack of ageing effect on leptin transport is distinct from other hormone systems such as prolactin where ageing markedly reduces the transport of prolactin into the brain. 15 Our findings are also in contrast to that of Banks et al, where 12-month-old CD-1 male mice showed impaired leptin transport, 43 which was accompanied by impaired leptin suppression of food intake. 44 Importantly, in that study, disrupted leptin transport and the satiety effects of leptin were specifically related to adiposity rather than ageing.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This lack of ageing effect on leptin transport is distinct from other hormone systems such as prolactin where ageing markedly reduces the transport of prolactin into the brain. 15 Our findings are also in contrast to that of Banks et al, where 12-month-old CD-1 male mice showed impaired leptin transport, 43 which was accompanied by impaired leptin suppression of food intake. 44 Importantly, in that study, disrupted leptin transport and the satiety effects of leptin were specifically related to adiposity rather than ageing.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple-time regression analysis was used to determine the unidirectional influx constant (K i ) from blood to brain as previously described for movement of protein into the brain. 5,15,16,25,26 An intravenous (i.v.) injection of 0.2 mL 10 6 counts per minute (cpm) of 125 I-leptin was administered into the left jugular vein of ketamine/ domitor anesthetised mice.…”
Section: Blood-brain Barrier Transport Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In male mice, prolactin is the only identified lactogen to act through the Prlr, with growth hormone failing to bind to the Prlr in mice (Bartke and Kopchick, 2015) and placental lactogen only relevant in female mice during pregnancy (Cohick et al, 1996). It has also been confirmed that circulating prolactin can be transported past the blood brain barrier to access central Prlrs (Brown et al, 2016b;Barad et al, 2020), with bromocriptine treatment significantly eliminating pSTAT5 expression in the brain (Brown et al, 2010). Therefore, we can be confident that prolactin acting at the Prlr is mediating the observed effect on paternal behavior in these mice.…”
Section: Discussionmentioning
confidence: 98%